Usage and attitude towards spoken English : A Preliminary survey - Azlina, Haji Arshad. (Universiti Malaysia Sarawak (UNIMAS), 1997)
The purpose of this study is to find out the UNIMAS Malay undergraduates' usage and attitudes towards spoken English; and the problems they encountered when using English in specific language situations that lead to infrequent use of spoken English. The respondents were one hundred Malay Undergraduates from Universiti Malaysia Sarawak. The instrument used in this study is a questionnaire. Data were analyzed using percentage. The results indicated that the Malay undergraduates who speak English at home use English more frequently in their daily communication. Majority of the Malay undergraduates have positive attitudes towards spoken English. However, low confidence in their own ability and a sense of unease, especially when engaging in spontaneous speech leads to the infrequent use of spoken English. Thus, Malay undergraduates need to gain intrinsic and extrinsic motivation, to encourage them to communicate frequently in spoken English.